Mengelola sistem pengendalian risiko operasional khas perbankan syariah - Rahim, Sabila Aulia (Maliki Interdisciplinary Journal, 2024)
Islamic banks face various types of risks specific to risk management issues. One of these is operational risk. Islamic banks need to look at operational risks that can affect their operational performance to achieve their operational objectives. Operational risks include losses caused by inadequacy or internal process failures, human error, and external events. To mitigate these operational risks, Islamic banks can implement operational risk management control systems, such as anticipating inherent risks, following the principles of the Islamic Financial Services Board (IFSB), and establishing internal controls for operational risks.